I would type this out, but you need to see something I cannot type. :)

LaughingFace Apr 25, 2018

#1**+2 **

I actually already have this answer!! Haha!! I figured it out!! Thanks though!

LaughingFace Apr 25, 2018

#4**+3 **

Don't worry about it, LF....as long as I can see it, the form doesn't matter

We can write the numerator as x^(5/2) y ^(3/2)

And the denominator is x^(2) y ^(3)

So....using a^{n} / a^{m} = a^{n-m} we have

x^(5/2 - 2) * y^ (3/2 - 3) =

x^(5/2- 4/2) * y^(3/2 - 6/2) =

x^(1/2) * y ( -3/2) ⇒ "B"

CPhill Apr 26, 2018